2018
DOI: 10.1111/risa.13111
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cancer‐Prevention Behavior: Disentangling the Effects of Risk Aversion and Risk Perceptions

Abstract: Experimental and survey research spanning the last two decades concludes that people who are more risk tolerant are more likely to engage in risky health activities such as smoking and heavy alcohol consumption, and are more likely to be obese. Subjective perceptions of the risk associated with different activities have also been found to be associated with health behaviors. While there are numerous studies that link risk perceptions with risky behavior, it is notable that none of these controls for risk avers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This is the first study employing population-level data to investigate the relationships between lifetime psychedelic use and lifetime diagnoses of either cancer in general or hematological cancer. We found that when compared to non-lifetime users, lifetime psychedelic users tended to have higher frequencies of a number of characteristics that have been associated with development of one or more cancer types including: male sex (Siegel et al, 2017), non-Hispanic white race/ethnicity (Siegel et al, 2017), never married or divorced marital status (Kato et al, 1989), more frequent risky behavior (Riddel and Hales, 2018), cocaine use and other stimulant misuse (Nelson et al, 1997), sedative and tranquilizer misuse (Iqbal et al, 2015; Kao et al, 2012), opioid use (Oh and Song, 2020), marijuana use (Ghasemiesfe et al, 2019), inhalant use (Haverkos, 1996), tobacco use (Hecht, 2003), residence in metropolitan areas (Zahnd et al, 2018), lifetime diagnosis of HIV/AIDS (Shiels and Engels, 2017), lifetime cirrhosis diagnosis (Ganne-Carrié and Nahon, 2019), lifetime diagnosis of hepatitis B or C (Ribes et al, 2008), and lower mean age of first alcohol use, suggesting heavier lifetime alcohol exposure (DeWit et al, 2000; Rehm et al, 2019). However, lifetime psychedelic users also tended to have a higher prevalence of some important protective factors for cancer, including younger age (White et al, 2014), lower BMI (Hulvat, 2020), higher educational attainment (Larsen et al, 2020), and higher income level (Larsen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study employing population-level data to investigate the relationships between lifetime psychedelic use and lifetime diagnoses of either cancer in general or hematological cancer. We found that when compared to non-lifetime users, lifetime psychedelic users tended to have higher frequencies of a number of characteristics that have been associated with development of one or more cancer types including: male sex (Siegel et al, 2017), non-Hispanic white race/ethnicity (Siegel et al, 2017), never married or divorced marital status (Kato et al, 1989), more frequent risky behavior (Riddel and Hales, 2018), cocaine use and other stimulant misuse (Nelson et al, 1997), sedative and tranquilizer misuse (Iqbal et al, 2015; Kao et al, 2012), opioid use (Oh and Song, 2020), marijuana use (Ghasemiesfe et al, 2019), inhalant use (Haverkos, 1996), tobacco use (Hecht, 2003), residence in metropolitan areas (Zahnd et al, 2018), lifetime diagnosis of HIV/AIDS (Shiels and Engels, 2017), lifetime cirrhosis diagnosis (Ganne-Carrié and Nahon, 2019), lifetime diagnosis of hepatitis B or C (Ribes et al, 2008), and lower mean age of first alcohol use, suggesting heavier lifetime alcohol exposure (DeWit et al, 2000; Rehm et al, 2019). However, lifetime psychedelic users also tended to have a higher prevalence of some important protective factors for cancer, including younger age (White et al, 2014), lower BMI (Hulvat, 2020), higher educational attainment (Larsen et al, 2020), and higher income level (Larsen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lifetime use of psychedelics, our logistic regression models also incorporated independent variables known to be associated with diagnoses of one or more cancers including age (White et al, 2014), sex (Siegel et al, 2017), race/ethnicity (Siegel et al, 2017), body mass index (BMI) (Hulvat, 2020), educational attainment (Larsen et al, 2020), income (Larsen et al, 2020), marital status (Kato et al, 1989), lifetime cirrhosis diagnosis (Ganne-Carrié and Nahon, 2019), lifetime diagnosis of hepatitis B or C (Ribes et al, 2008), lifetime history of HIV/AIDS (Shiels and Engels, 2017), rural versus urban location of residence (Zahnd et al, 2018), lifetime marijuana use (Ghasemiesfe et al, 2019), lifetime heroin and prescription opioid use (Oh and Song, 2020), lifetime sedative and tranquilizer use (Iqbal et al, 2015; Kao et al, 2012), lifetime cocaine and other stimulant use (Nelson et al, 1997), and lifetime inhalant use (Haverkos, 1996). Health insurance status, an important factor in determining access to cancer screening (Zhao et al, 2018), and risk taking behavior, important given its relationship to cancer prevention behaviors (Riddel and Hales, 2018), were included as well. Tobacco use (Hecht, 2003) was incorporated into the model using variables assessing lifetime use of smokeless tobacco, lifetime use of pipe tobacco, lifetime use of cigars, and whether the participant had ever smoked cigarettes daily for 30 days consecutively (a preferable variable for capturing the carcinogenic risk of smoking compared to lifetime use of cigarettes).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the literature suggests that smokers are generally more inclined to have a lifestyle linked to risk and uncertainty (i.e., less risk averse) than non-smokers(Coletta et al 2018;Riddel and Hales 2018).6 Commission Regulation (EU) No 432/2012 of 16 May 2012 establishing a list of permitted health claims made on foods, other than those referring to the reduction of disease risk and to children's development and health.…”
mentioning
confidence: 99%
“…Consistent with increased prospection, the active conditions in both methods demonstrated greater risk avoidance. Increased risk-prevention focus has been significantly related to positive health behavior change as well, even when holding factors such as optimism constant [ 30 ]. Reward focus was not significantly different between the active and the control conditions for either method, although a greater focus on reward approached significance for FTP.…”
Section: Discussionmentioning
confidence: 99%